Упростить выражение: а)cos^2t*tg^2t-sin^2t*cos^2t б)1-сos^2+tg^2t*cos^2t в)(1-sin^2t)*(tg^2t+1) г)(1-cos^2t)*(ctg^2t+1)

Упростить выражение: а)cos^2t*tg^2t-sin^2t*cos^2t б)1-сos^2+tg^2t*cos^2t в)(1-sin^2t)*(tg^2t+1) г)(1-cos^2t)*(ctg^2t+1)
Гость
Ответ(ы) на вопрос:
Гость
а) [latex]cos^{2} t*tg^{2} t-sin^{2}t*cos^{2} t= \frac{cos^{2}t*sin^{2}t}{cos^{2}t }-sin^{2}t*cos^{2}t=[/latex] [latex]sin^{2} t-sin^{2}t*cos^{2}t=sin^{2}t*(1-cos^{2}t)=sin^{2}t*sin^{2}t=sin^{4}t[/latex] б) [latex]1-cos^{2}t+tg^{2}t * cos^{2}t=sin^{2} t+ \frac{sin^{2} t*cos^{2}t }{cos^{2}t }=sin ^{2} t+sin^{2} t=2sin^{2} t[/latex] в) [latex](1-sin^{2}t)*(tg^{2}t+1)=cos^{2}t*( \frac{sin^{2t} }{cos^{2}t } +1)=sin^{2}t+cos^{2}t=1 [/latex] г) [latex](1-cos^{2} t)*(ctg^{2}t+1)=sin^{2}t*( \frac{cos^{2}t }{sin^{2}t } +1)=cos^{2}t+sin^{2}t=1 [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы